The impact of playoffs on seasonal uncertainty in the Czech Ice Hockey Extraliga - Lahvicka, J. (Journal of Sports Economics, 2015)
In the top Czech ice hockey competition "Extraliga," 14 geographically close teams compete during a regular season in a pure round-robin tournament. However, the eventual champion is determined in the additional playoff stage and the regular season just decides which teams qualify for the playoffs and how these teams are seeded. This article uses a Monte Carlo simulation to show that although the additional playoff stage heavily favors higher-seeded teams and consists of a lot of games, it lowers the average probability of the strongest team becoming a champion from 48 to 39% and thus increases seasonal uncertainty.